A scientometric review of global research on technology in physical education - Daharis; Novri Gazali; Feby Elra Perdima; Khairul Hafezad Abdullah; Ahmad Rahmadani (UIR Press, 2023)
Since COVID-19, technology-based physical education has been normal and is emerging. This paper is intended to identify the development of scientific publications and map educational technology research pertinent to physical education. The keywords